A moving target: The geographic evolution of Silicon Valley, 1953–1990. Issue 6 (18th August 2018) - Adams, Stephen B.; Chambers, Dustin; Schultz, Michael
Abstract: This article provides an empirical examination of high-tech firm location data from 1953 to 1990 to show a dramatic shift in geographic centre of what is now called Silicon Valley. Universities (most notably Stanford), venture capital and law firms acted as magnets for divisions of established firms and local start-ups. These institutions combined with the Santa Clara County's available land to pull the high-tech region's epicentre south-eastwards from San Francisco, an early source of investment capital and legal expertise. These findings add another element (spatial change) for consideration in explaining the evolution of industry clusters.